Energy Metabolism in the Normal and in the Diabetic Heart - Barsotti, Antonio; Giannoni, Alberto; Di Napoli, Pericle; Emdin, Michele (Current Pharmaceutical Design, 2009)
Cardiovascular disease is a major health problem all over the world. The prevalence of type 2 diabetes mellitus has been rapidly increasing, together with the risk of cardiovascular events. Patients with diabetes, and/or with insulin resistance as well, have an impaired myocardial metabolism of glucose and free fatty acids (FFA) and accelerated and diffuse atherogenesis, with involvement of coronary artery tree. Significant metabolic alterations at heart level in diabetic patients are the decreased utilization of glucose and the increase in muscular and myocardial FFA uptake and oxidation, occurring as a consequence of the mismatch between blood supply and cardiac metabolic requirements. These metabolic changes are responsible both for the increased susceptibility of the diabetic heart to myocardial ischemia and for a greater decrease of myocardial performance for a given amount of ischemia, compared to non diabetic hearts. A therapeutic approach aimed at an improvement of cardiac metabolism, through manipulations of the utilization of metabolic substrates, may improve myocardial ischemia and left ventricular function. Modulation of myocardial FFA metabolism, in addition to optimal medical therapy, should be the key target for metabolic interventions in patients with coronary artery disease and diabetes. In diabetic patients with ischemic heart disease, the effects of modulation of FFA metabolism could even give greater benefit than in nondiabetic patients.
Keywords: Diabetic Heart